2024
DOI: 10.2174/1573397118666220527140626
|View full text |Cite|
|
Sign up to set email alerts
|

WITHDRAWN: Neuropathic Pain in Patients with Knee Osteoarthritis: Relation with Comorbidities and Functional Status

Abstract: Objectives: The aim of this study was to evaluate the prevalence of neuropathic pain components of knee osteoarthritis (OA) patients and to identify the relation between associated neuropathic pain and comorbidities, pain intensity, function, and radiographic severity of knee OA. Methods: This cross-sectional study enrolled patients with knee OA (ACR criteria 1986). Visual Analog Scale (VAS), DN4 questionnaires were performed for each patient. A score of DN4≥4/10 was classified as diagnostic for neuropathic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…We observed several person-level but few foot-level differences between participants with and those without neuropathic pain. Those with neuropathic pain had worse general health (demonstrated by lower SF-12 scores) and greater pain severity, which is consistent with previous reports related to neuropathic pain in individuals with knee OA using a range of health-related quality of life measures (11,13,14) and pain assessment tools (7,8,10,15). Interestingly, we found that although pain severity at rest was higher in those with neuropathic pain, pain during walking was not.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We observed several person-level but few foot-level differences between participants with and those without neuropathic pain. Those with neuropathic pain had worse general health (demonstrated by lower SF-12 scores) and greater pain severity, which is consistent with previous reports related to neuropathic pain in individuals with knee OA using a range of health-related quality of life measures (11,13,14) and pain assessment tools (7,8,10,15). Interestingly, we found that although pain severity at rest was higher in those with neuropathic pain, pain during walking was not.…”
Section: Discussionsupporting
confidence: 91%
“…The presence of neuropathic symptoms increases the individual burden of knee OA, as it is associated with more severe pain ( 7 , 8 , 9 , 10 ), greater impairment in physical function ( 9 , 10 , 11 , 12 , 13 ), worse quality of life ( 10 , 11 , 13 , 14 ), and poorer sleep quality ( 10 ). Several person‐level factors are associated with neuropathic pain in individuals with knee OA, including increased age ( 13 ), higher body mass index (BMI) ( 13 ), female sex ( 8 ), multiple comorbidities ( 8 ), pain at multiple sites ( 7 , 12 ), referred pain ( 7 ), and hyperalgesia ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 , 10 Some sinuses heal with scarring while new sinuses emerge elsewhere, leading to gruesome deformity of the affected limb. 16 , 18 , 19 , 20 , 21 Despite its several worrisome impacts, simple mentioning of mycetoma still leads astonishment. This is probably owing to poor awareness of its existence as a consequence of low identification and reporting as it is not a reportable disease.…”
Section: Discussionmentioning
confidence: 99%
“…The causative organisms trigger the formation of grains that may be discharged into the skin surface through multiple sinuses 7,10 . Some sinuses heal with scarring while new sinuses emerge elsewhere, leading to gruesome deformity of the affected limb 16,18‐21 . Despite its several worrisome impacts, simple mentioning of mycetoma still leads astonishment.…”
Section: Discussionmentioning
confidence: 99%